IMPROVING THE SKILL OF ANTICIPATING FALLING PULLS USING “GUNTINGAN” ON PENCAK SILAT ATHLETES (Study Action Research at PPLM DKI Jakarta) - Saputro, Eko Novian; Widiastuti; Setiakarnawijaya, Yasep; Subandi, Oman Unju (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This study aims to improve the skills of anticipating falling pulls using “guntingan” on pencak silat athletes of the Jakarta Student Sports Education and Training Centre (PPLM). This research was carried out from March to May 2024 at the Gymnasium of Jakarta State University. The study was attended by all Jakarta PPLM pencak silat athletes in the competition category totalling 15 athletes, consisting of 10 male athletes and 5 female athletes. The method used in this study is Action Research with a one group pre-test post-test design. The instrument used is a test of the skill of anticipating falling pulls using “guntingan” that have been validated by experts and martial arts experts. Based on the pre-test data of the skill of anticipating falling pulls using “guntingan”, an average result of process correctness was 88.4% and an average success rate of 31.3%. Then after being given exercise material in research to improve the ability of pull fall anticipation skills using “guntingan” for 8 meetings, a post-test was carried out with an average result of 96.5% process correctness and an average success rate of 87.3%. There is an improvement in both the correctness of the process and the success rate. This research is completed in one cycle and does not need to continue to the next cycle. Because the problem has been answered, through research can improve the skill of anticipating falling pulls using “guntingan” on pencak silat athletes (study action research at PPLM DKI Jakarta).